Ghana - International Competitiveness : Opportunities and Challenges Facing Non-Traditional Exports - World Bank (Washington, DC, 2013)
The report first reviews macroeconomic aspects in Ghana, identifying that much of the non-traditional exports' expansion, reflects sporadic foreign investments in key agro-processing activities - which enjoy preferential treatment in European markets - but, its value-added seems at best marginal, questioning its sustainability, should preferences be removed. Besides compliance with a growing number of European Union regulations on environmental, and food safety standards, Ghana will need to create a favorable business environment to attract foreign investment, and raise competitiveness of exporting firms. The study then analyzes microeconomic competitiveness, through four case studies on natural resource-based exports; efficient import substitution, and expansion into regional markets; labor-intensive, light manufactures and services; and, culture and arts manufactures. Constraints identified by exporters are industry specific, while, main cross-cutting issues, relate to the trade regime, and the provision of infrastructure. Findings of this report suggest that an export strategy for a country at Ghana's stage of development, should be based on two basic principles: maximizing the returns to current comparative advantage; and, over time, "catalizing" export diversification towards more sophisticated sources of advantage.